2009
DOI: 10.1111/j.1601-5223.1979.tb01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual functions, semen characteristics and fertility of bulls carrying the 1/29 chromosome translocation

Abstract: Twelve bulls carrying the 1/29 chromosome translocation were compared with 45 chromosomally normal bulls concerning sexual functions, semen characteristics, and fertility. All bulls were unselected from the point of view of fertility. Sexual functions such as libido and serving ability were found to be quite normal in bulls carrying the 1/29 chromosome translocation. The semen analysis indicated small reductions in the concentration of semen and in the total number of spermatozoa but the volume of the ejaculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Nevertheless, some data suggest that the percentage of unbalanced gametes is higher in cows than in bulls heterozygous for the t(1; 29). Indeed, fertility criteria (calving intervals, non-return to service rate, culling rate) are more depressed for the t(1; 29) carrier cows than for the mates of carrier bulls (Refsdal, 1976;Dyrendahl and Gustavsson, 1979;Maurer and Vogt, 1988). Moreover, the study of Schmutz et al (1991) indicated that the percentage of unbalanced embryos is higher if they are produced by carrier cows (36%) than by carrier bulls (19%).…”
Section: Meiotic Segregation Analysis In Cows Carryingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some data suggest that the percentage of unbalanced gametes is higher in cows than in bulls heterozygous for the t(1; 29). Indeed, fertility criteria (calving intervals, non-return to service rate, culling rate) are more depressed for the t(1; 29) carrier cows than for the mates of carrier bulls (Refsdal, 1976;Dyrendahl and Gustavsson, 1979;Maurer and Vogt, 1988). Moreover, the study of Schmutz et al (1991) indicated that the percentage of unbalanced embryos is higher if they are produced by carrier cows (36%) than by carrier bulls (19%).…”
Section: Meiotic Segregation Analysis In Cows Carryingmentioning
confidence: 99%
“…Previous studies (Gustavsson, 1969(Gustavsson, , 1971Refsdal, 1976;Dyrendahl and Gustavsson, 1979) demonstrated the negative effect (3-5%) of this translocation on reproductive performance of both male and female heterozygotes. By using the sperm-FISH technique our recent study revealed that, on average, 97.1% of spermatozoa were normal or balanced in the semen of t(1; 29) carrier bulls (Bonnet-Garnier et al, 2006).…”
Section: Meiotic Segregation Analysis In Cows Carryingmentioning
confidence: 99%
“…taurus). Numerous studies provide evidence for the role of Robertsonian translocations in reduced fertility (in vitro: Kawarsky et al 1996, Rubes et al 1999, in vivo: Gustavsson 1969, Dyrendahl and Gustavsson 1979, Rangel-Figueiredo and Iannuzzi 1991. Despite being phenotypically normal, translocation carriers experience a decrease in reproductive potential, predominantly due to the production of chromosomally unbalanced gametes which, subsequent to fertilization, result in early embryonic death (Popescu 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Deviations of the non-return rate of cows, daughters of translocation carriers, could be attributable to early embryonic mortality due to unbalanced chromosome sets of the zygote forming gametes. Although chromosomally unbalanced gametes were produced for 1; 29 carrier bulls (Logue and Harvey, 1978), no deviation of their semen picture was suggested (Dyrendahl and Gustavsson, 1979). Synaptonemal complex analysis of the 1; 29 translocation and more recent mitotic chromosome analyses have demonstrated that the chromosome event in question could involve more than one structural chromosome rearrangement (Di Meo et al, 2006).…”
Section: Pairing Failure Of Translocated Chromosomes: Cause or Effectmentioning
confidence: 99%